Capturing nursing history : a guide to historical methods in research - Lewenson, Sandra; Herrmann, Eleanor Krohn (Springer Pub., 2008)
While research texts abound in the nursing literature and nursing history fields, there has been no hands-on text for describing the process of doing historical research. This book, written by well known and respected nurse historians, will provide the necessary direction, guidance, and examples needed to conduct historical research. Features of this edition: Provides direction and tools for conducting historical research Describes types of research including biographic and oral histories Covers frameworks used to study historical events, such as social, political, feminist, intellectual, a.